Optimized Distribution of Beijing Population Based on CA-MAS - Haoguang Liang; Zhong Wang (Discrete Dynamics in Nature and Society)
In recent years rapid expansion of populations, disruption of ecological environments, and power shortages to areas of high population density in undeveloped areas have appeared in major cities in China. Well-planned population distribution in a city has become one of the key development strategies of urbanization in the country. Taking Beijing as a case-study and using 2010 as the base period, this study simulates city population size and distribution during 2011–2030 using the CA-MAS model. The results showed that (1) the unplanned layout of Beijing’s population is inefficient and will result in the slow agglomeration of populations into surrounding small towns, (2) the suburbanization of the population (while employment opportunities remain centralized) increases the stress of the city commuters, (3) the current policy guiding the distribution of residential and commercial areas is effective, accelerating the formation of small town clusters, which play a role in the city’s radiation and diffusion, contributing to reducing urban commuter stress, and (4) promoting the homogenization of public resources, planning the development of a multicenter urban area, and promoting mixed use (commercial and residential) zoning are the main measures recommended to strengthen the sustainability of Beijing’s urban development and to optimize spatial layout.